STUDIES ON FISH EGGS AND LARVAE FROM INDIAN WATERS 2. DEVELOPMENT OF EGG AND LARVAE OE ACENTROOOBIUS ORNATUS (RtFPPELL) - Vijayaraghavan, P (Indian Journal of Fisheries, 2011)
Eggs of Acentrogobius ormtus (Riipp.), attached to Placenta shells were collected along with the parent (male) fish guarding it in knee deep water from the Vellar estuary at Portonovo. The embryonic development from the blastoderm stage up to hatching and the larvae up to the seventh day are described. Besides the present account on A. ornatus, the eggs and early development of its congeners, ^ . n«7/i and/4. v/»-/uncra/«;s have been known. The eggs of<4.ne///j is club shaped and smaller than that of A. ormtus which is stumpy, broader at the base arid is the smallest of all. In A. ormtus o&mA. viridipunctatusths oil globules do not coalesce to form a single one as met with in A. neilli. The egg of y4. ornatus which is the smallest of the three species, has the longest period of incubation. The important features in the embryonic and larval development of the three species are tabulated for comparison.